Depth determination of underground pipe in different type of soil by using high and low frequency of ; GPR / Suhaida Suamkah - Suamkah, Suhaida (2018)
Pipe detection is most crucial aspect that had to be taken in order to carry any activities on the ground. It is an important role to choose the best, correct type of instrument used in detecting the location, position and depth of the underground pipe for further work based on the type of the soil where the pipe was buried. Other than that, in order to investigate the pipes, a destructive technique is often used (Jones, 1982). So, the surveyed area was being damaged and destroyed. By using the GPR observation method, any destruction on the site can be prevented. In order to avoid from destroying the surrounding area, a precise digging planning can be obtained by using GPR device (Sepp, E. M., & Colonel, L., 2000). This study is done by comparison method where the depth of the underground pipe obtained from GPR observation for both frequencies will be compared with the depth obtained from leveling method. The depth comparison is applied for each of the type of the soil.